SA119. Defeatist Attitudes and Self-Stigma Associations in Patients With Schizophrenia - Mikhael, Tanya (Schizophr Bull, 2017)
Background: Recent research has explored relationships among stigma, self-esteem, defeatist performance attitudes, and outcomes in schizophrenia. Internalized stigma has been associated with diminished self-esteem, hopelessness, and defeatist performance attitudes that have been associated with symptoms and poor functioning in schizophrenia. Internalized stigma can be viewed as self-defeating beliefs linked to illness, whereas defeatist attitudes as measured with the Defeatist Performance Attitude Scale (DPAS) are more generalized defeatist beliefs that may come from self-stigma related to illness as well as other factors such as failure experiences that are not attributed to illness. Methods: This study examined the relationships between these constructs as measured by the DPAS (Cane, Olinger, Gotlib, & Kuiper, 2006), the short form of the Self-Stigma of Mental Illness Scale (SSMIS-SF) and the Self-Esteem Rating Scale (SERS), and the Beck Hopelessness Scale (BHS). Participants (N = 60) enrolled in a randomized clinical trial for older adults with schizophrenia (mean age = 56) completed these assessments along with a battery of symptom, functioning, and neuropsychological measures. Results: Defeatist attitudes were moderately correlated with the Apply to Self (r = .453, P = .000), and Harm to Self-Esteem (r = .349, P = .006) subscales of the SSMIS-SF as well as both SERS subscales (positive: r = −.332, P = .002, negative: r = .461, P = .000), hopelessness (r = .391, P = .000), positive symptoms (Positive and Negative Syndrome (PANSS) positive subscale: r = .421, P < .001), and performance-based functioning (Maryland Assessment of Social Competence: r = −.274, P = .013). Both subscales of the SSMIS were correlated with SERS positive (r = −.454, P = .000, = −.419, P = .001) and negative (r = .553, P = .000, r = .552, P = .000) self-esteem, hopelessness (r = .335, P = .000, r = .372, P = .000), and positive symptoms (r = .256, P = .048, r = .308, P = .017). Simultaneous regressions with both SSMIS subscales and DPAS as predictors were significant only for SERS positive (R(2) = .226, F(3, 55) = 5.342, P < .003) and SERS negative (R(2) = .385, F(3, 55) = 11.467, P < .000) self-esteem, hopelessness (R(2)=.216, F(3, 55) = 5.036, P < .004), and PANSS positive symptoms(R(2) = .159, F(3, 56) = 3.540, P < .020). In these models, defeatist attitudes, but not the stigma subscales, were a significant independent predictor of SERS negative (but not positive) self-esteem (βstd = .271, P = .027), hopelessness (βstd = .284, P = .039), and positive symptoms (βstd = .283, P = .044). Conclusion: Thus, despite some overlap between these constructs, generalized defeatist beliefs were a stronger predictor of important outcomes in schizophrenia than self-stigma. These findings suggest, while both types of defeatist attitudes can be productive targets for interventions such as cognitive behavior therapy, reducing severity of more generalized defeatist attitudes may produce better outcomes.